Asymmetric synthesis of beta-amino acid scaffolds - Bull, S; Davies, S; Smith, A (2001)
Addition of two or three equivalents of lithium (S)-N-benzyl-N-α-methylbenzylamide to conjugate acceptors containing two or three α,β-unsaturated ester fragments respectively and subsequent hydrogenolytic deprotection afford homochiral bis- or tris-β-amino esters containing two or three new stereogenic centres in high de and ee.